Analysis of Five-Year Trend of Malaria at Bichena Primary Hospital, Amhara Region, Ethiopia. (29th January 2021) - Minwuyelet, Awoke; Aschale, Yibeltal
Abstract : Background . Malaria is a life-threating infectious diseases caused by protozoan parasite of the genus Plasmodium. The WHO African region bears the largest burden of malaria morbidity and mortality every year. Prevention and control activity of malaria in Ethiopia is implemented as guided by a national strategic plan to decrease malaria burden. This study is aimed at assessing the five-year trend of malaria at Bichena Primary Hospital. Method . A retrospective study was conducted at Bichena Primary Hospital to assess the five-year (2015-2019) trend of malaria by reviewing blood film reports from a laboratory logbook. Result . In a five-year period, 9182 blood films were requested for malaria diagnosis of whom 53.8% were males and 41% were in the age group 15-29. The overall prevalence of malaria was 9.28% (n = 852 ), P. falciparum being the dominant malaria species. The highest peaks of total malaria cases were observed in 2016 and in December, and the lowest peaks were observed in 2018 and March (mean annual case 170.4; mean monthly case 14.2), and there was a statistically significant year and monthly variation of malaria cases (P < 0.001 ). Malaria was reported in both sexes and all age groups; of which, males and the age group 15-29 years old consist the highest number of malaria cases (P < 0.001 ). Conclusion . Malaria remains an important public health problem in the study area, and a significant fluctuation was noticed in a five-year period, P. falciparum being slightly the dominant malaria species. Successive efforts are still required to reduce malaria burden to a level that has no longer public health effect.